Relationships between high-stakes testing policies and student achievement after controlling for demographic factors in aggregated data. - Marchant, Gregory J.; Paulson, Sharon E.; Shunk, Adam (Education Policy Analysis Archives, 2006)
With the mandate of No Child Left Behind, high-stakes achievement testing is firmly in place in every state. The few studies that have explored the effectiveness of high-stakes testing using NAEP scores have yielded mixed results. This study considered state demographic characteristics for each NAEP testing period in reading, writing, mathematics, and science from 1992 through 2002, in an effort to examine the relation of high-stakes testing policies to achievement and changes in achievement between testing periods. As expected, demographic characteristics and their changes were related significantly to most achievement outcomes, but high-stakes testing policies demonstrated few relationships with achievement. The few relationships between high-stakes testing and achievement or improvement in reading, writing, or science tended to appear only when demographic data were missing; and the minimal relationships with math achievement were consistent with findings in previous research. Considering the cost and potential unintended negative consequences, high-stakes testing policies seem to provide a questionable means of improving student learning.